Case Report: Multi-Modality Imaging of a Right Atrial Pseudoaneurysm in a Patient With Breast Cancer - Zhong, Ying; Ma, Chun-yan; Dai, Xu; Wang, Guan (Frontiers in Cardiovascular Medicine, 2021)
Cardiac pseudoaneurysms occur when a blood vessel wall is injured and the leaking blood is collected in the surrounding tissue. They are very rare events and have a high risk of rupture and poor prognosis. We report a case of right atrial pseudoaneurysm in a 54-year-old female patient diagnosed with breast cancer and lung metastasis. The patient underwent five intrapericardial infusions of cisplatin and nine cycles of systemic chemotherapy. Non-contrast-enhanced computed tomography (CT) was performed at follow-up evaluation during the chemotherapeutic process as this patient was contraindicated to iodine. CT without contrast and ultrasonography showed a crescent-shaped lesion near the right atrium but its nature could not be determined. Cardiac magnetic resonance (CMR) imaging with gadolinium contrast provided important information as an alternative enhanced imaging modality. By combining CT, ultrasonography and CMR images with the medical history of the patient, we inferred that the lesion was a pseudoaneurysm in the right atrium. This condition was related to the erosion of metastasized tumor cells or the accumulated cardiac toxicity of multiple cycles of chemotherapy or pericardiocentesis. This single case report suggests that cardiac rupture should be considered as a potential complication in patients with suspected pericardial metastasis. CMR imaging is an excellent tool for the detection of right atrial rupture.